The inventions that changed the world : (Readers' Digest Association, 1982)
The Inventions that Changed the World describes more than 400 of mankind's key inventions, it tells how and where they were conceived, and it explains how they have changed the society into which they were orn. It includes stories of brilliance of triumphant success and bizarre failure, and of the unquenchable optimism of...